Correlations of passes and playing formations with technical-tactical elements during the 2022 FIFA World Cup - Michailidis, Y.; Nenos, I.; Metaxas, I.; Mandroukas, A.; Metaxas, T. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: This study on the 2022 Qatar FIFA World Cup examined: a) the existence of correlations between passes with other technical-tactical elements, b) the differences in technical-tactical elements in relation to team formation, and c) the characteristics of the key passes created during games. METHODS: Sixty-four games were analyzed. Match-analysis data were collected using InStat database. RESULTS: Spearman correlation revealed that the number of passes and key passes correlated with number of goals, chances and shots (P<0.05). Team ball possession was correlated with number of passes, key passes, chances, shots and the organized attacks (P<0.001). Kruskal-Wallis H non-parametric test revealed that the teams with the higher percentages of team ball possession, and the higher number of chances, shots and crosses used formations 1-4-2-3-1 and 1-4-3-3. Finally, most of the key passes performed in axis of the field and they were short low passes. CONCLUSIONS: The ability of teams to keep the possession of the ball, looking for the key pass, and final action can be a factor in the team`s success. A characteristic finding of the study was the preference of groups to manifest their attack from the axis. The equal distribution of attacks between the axis and the sides of the field makes the team`s offensive function more unpredictable. Also, most formations concentrate several players on the axis, making it more difficult to complete an attack from this area.